Metabolic Reprogramming of Sulfur in Hepatocellular Carcinoma and Sulfane Sulfur-Triggered Anti-Cancer Strategy - Zhang, Ximing; Chen, Mianrong; Ni, Xiang; Wang, Yingying; Zheng, Xue; Zhang, Hui; Xu, Shi; Yang, Chun-tao (Frontiers in Pharmacology, 2020)
Metabolic reprogramming is a cancer hallmark. Although the reprogramming of central carbon has been well documented, the role of sulfur metabolism has been largely overlooked. Additionally, the effects of sulfur are sometimes contradictory in tumorigenesis. In this study, we aimed to investigate the gene expression profile in hepatocellular carcinoma (HCC) and the effects of reactive sulfur species (RSS) on HCC tumor cells. Furthermore, the cell imaging technology was applied to discover some potential anti-cancer compounds. Gene Set Enrichment Analysis (GSEA) of Gene Expression Omnibus (GEO) dataset (GSE102083) revealed that sulfur amino acid-related metabolism and vitamin B6’s binding activity in HCC tissues were downregulated. Calculation of the interaction network identified nine hub genes, among which eight were validated by differential expression and survival analysis in the TCGA_LIHC cohort, and two (CSE and CBS) had the highest enrichment degree. The metabolomics analysis suggested that the hub genes were associated with RSS metabolism including H2S, H2S2, cystine, cysteine, homocysteine, cystathionine, and methionine. The cell viability assay demonstrated that H2S2 had significant anti-cancer effects in HCC SNU398 tumor cells. The cell imaging assay showed that treatment with H2S2 remarkably increased intracellular sulfane sulfur content. On this basis, the anti-cancer activity of some other sulfane sulfur compounds, sucha as DATS and DADS, was further verified. Lastly, according to the fact that HCC tumor cells preferentially take in cystine due to high expression of SLC7A11 (a cystine/glutamate transporter), persulfided cysteine precursor (PSCP) was tested for its sulfane sulfur release capability and found to selectively inhibit HCC tumor cell viability. Collectively, this study uncovered sulfur metabolism in HCC was reprogrammed, and provided a potential therapeutic strategy for HCC by donating sulfane sulfur.